Uji Efek Antifungi Ekstrak Daun Biduri (Calotropis Gigantea L.) Terhadap Pertumbuhan Jamur Trichophyton Mentagrophytes - Safrida Safrida; Rosa Mardiana; Nurul Husna (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The leaf of biduri (Calotropis gigantea L.) is one of the plants that can be used as antifungal. Biduri leaves are used as antifungals based on the chemicals contained in them such as tannins, flavonoid saponins and polyphenols. The fungus Trichophyton mentagrophytes can cause a skin disease characterized by the appearance of circular and scaly patches or small bubbles known as Tinea or ringworm. This fungus has a habitat (especially in tropical and wet climates) in soil, humans and animals. This study aims to determine the effectiveness of biduri leaf extract (Calotropis gigantea L.) in inhibiting the growth of the fungus Trichophyton mentagrophytes and to determine what is the optimal concentration of biduri leaf extract (Calotropis gigantea L.) to inhibit the growth of the fungus Trichophyton mentagrophytes. This research was carried out at the Microbiology Laboratory of the Tarbiyah Faculty of UIN Ar-Raniry and the Chemical Laboratory of the Chemical Science Faculty, Syiah Kuala University, Banda Aceh, from 26 April to 21 August 2018. Biduri leaves were extracted using the maceration method which were soaked for 5 days with 2 repetitions and evaporated with using a rotary evaporator to obtain extract as much as 30 ml blackish green and thick. Inhibition test against the fungus Trichophyton mentagrophtes was carried out using the disc diffusion method on Potato Dextrose Agar (PDA) media with concentrations of 20%, 35% and 50%. Ketoconazole antifungal was made in suspension form as a positive control and aquadest as a negative control. The results showed that the diameter of the inhibition zone obtained from biduri leaf extract at a concentration of 50% of 9.16 mm was included in the medium category, at a concentration of 35% of 8.66 mm was included in the medium category, 20% concentration of 8.16 mm was included. in the medium category, 11.83 mm of ketoconazole suspension was included in the strong category and 0 mm of aquadest which had no inhibitory power.